CSN6 aggravates inflammation and Myocardial injury in macrophage of sepsis model by MIF - Qianying Song; Changming Zhou; Yufei Liu; Liping Wang; Huiyi Lv; Cuiying Zhang; Xuanqi Wang (Scientific Reports)
Abstract Sepsis, one of the leading causes of death in critically ill patients, is characterized by multiple organ dysfunction due to a dysregulated immune response to infection. Caregivers closely monitor patients’ organ function indicators in the intensive care unit,which is essential for the early identification and management of organ dysfunction cauxsd by sepsis. Hence, we investigated the effects of CSN6 on sepsis and its underlying mechanism. RAW264.7 cell inducted with lipopolysaccharide (LPS) and adenosine triphosphate (ATP). CSN6 protein expression increased in an in vitro model of sepsis. We collected samples from 10 sepsis patients (It was collected under strict compliance with ethical norms and nursing procedures) and performed single-cell analysis for CSN6 expression. CSN6 aggravated macrophage inflammation in an in vitro model of sepsis. CSN6 aggravated macrophage ferroptosis in an in vitro model of sepsis. CSN6 aggravates mitochondrial damage in an in vitro model of sepsis. CSN6 induces MIF expression in macrophages in an in vitro model of sepsis. MIF inhibitors reduced the effects of CSN6 on inflammation and ferroptosis in an in vitro sepsis model. CSN6 protein at 11-ARG, 21-ARG, 31-LEU, and 32-ASP linked to MIF protein at 280-ASN and 366-SER. In conclusion, CSN6 appears to aggravate inflammation in macrophages in a sepsis model via MIF signaling. This finding suggests that future therapeutic strategier targeting the CSN6 and MIF pathways may require nurses to closely monitor changes in inflammatory responses and potential treatment side effecta at the bedside. Further research involving in vivo models, such as examining CSN6 and MIF expression levels in macrophages or monocytes from sepsis and control mice, is essential to fully confirm these findings and establish the therapeutic potential of targeting the CSN6/MIF axis in sepsis. The nursing research team plays a key role in translating basic research findings into clinical practice,including the developpment of early warning tools and individualized management programs based on these biomarkers.